Expansion characteristics of concrete with free lime based expansive additives under uniaxial restraint conditions. (21st November 2022) - Gupta, Mayank; Pen, Kolneath; Igarashi, Go; Takahashi, Yuya; Ishida, Tetsuya
Highlights: Concrete expansion due to expansive additives in reinforced concrete has been studied. Expansions decrease in restrained directions but remain unchanged in the free direction. Volumetric expansion decreases with an increase in the reinforcement ratio. Expansion characteristics of expansive concrete have been compared with that of ASR and DEF. Abstract: Expansive additives in higher dosages induce chemical prestress in concrete by imparting higher early-age expansion. However, induced stress and concrete expansion can vary significantly, depending on different restraint conditions. In addition, concrete expansion can be highly anisotropic depending on the nature of external restraints and boundary conditions. Experimentations have been performed to study the effect of uniaxial (anisotropic) restraint on the concrete expansion (in both restraint and stress-free directions) and induced prestress. A higher degree of restraint resulted in a substantial decrement in the longitudinal expansion. In contrast, expansion in the stress-free (lateral) direction was not much affected by the restraint in other direction. As a result, an overall decrement in the volumetric expansion was observed with an increase in the reinforcement ratios. Stress induced in concrete due to the restraint expansion in the longitudinal direction was found to be higher for a higher reinforcement ratio. Data provided from the current work can be used for the comprehensive modelling of expansive concrete under external restraints.